Fuel cell science : theory, fundamentals, and biocatalysis - Wieckowski, Andrzej, 1945-; N{u2CEB}ov, J. K. (Jens K.) (Hoboken, N.J. : Wiley, 2010)
'This book provides a modern problem-solving compendium to help meet challenges in fuel cell science and technology worldwide. Along with the scientific foundation of this technology, the coverage includes recently developed strategies for the design, preparation, and characterization of catalytic materials for fuel cell electrodes, especially for new fuel cell cathodes. The methodology described includes a wide spectrum of methods for spurring new fuel cell catalysis concepts and improving existing designs to increase their performance. This is a key resource for a wide range of engineering and research scientist, professionals, and entrepreneurs'--
'The objective of this book is to provide a modern, comprehensive problem-solving compendium that can help us to meet meet present and upcoming challenges in fuel cell science and technology worldwide'--
Includes bibliographical references and index.
Keywords: Fuel cells; Enzymes